Neonatal femoral artery thrombosis at the time of birth: a case report - Orestis Tsonis; Thodoris Gouvias; Fani Gkrozou; Ioanna Antonopoulou; Anastasia Giantsouli; Minas Paschopoulos; Maria Baltogianni (Hygeia Press di Corridori Marinella, 2020)
Neonatal thrombosis is a relatively common disease/condition and most often associated with predisposing genetic factors, underlying medical disorders and acquired trigger factors, such as iatrogenic interventions. Perinatal femoral artery thrombosis with no underlying risk factors has not been presented in the international literature. There has been no evidence of perinatal artery thrombosis with no underlying risk factors in the international literature. In this case presentation, a neonate was born via normal vaginal delivery at 39+4 weeks of gestation, in an otherwise uncomplicated pregnancy without risk factors, with marked discoloration of right lower abdomen and right lower limb, initially pale and eventually evolving to cyanotic. At the time of birth, such clinical presentation was a challenge to clinicians regarding diagnosis. The absence of right-sided palpable femoral pulses raised suspicion and led to a diagnostic approach primarily including ultrasonography. A right femoral blood clot blocking blood flow and resulting in the pale right lower limb was revealed via Doppler ultrasound. Screening test for thrombophilia was negative and neonatal arterial patency was achieved after administration of Low Molecular Weight Heparin (LMWH). After a 6-week course of treatment, vascular latency was fully restored and confirmed by ultrasound on day 10 post-partum. Clinicians should be aware of this unusual event that can be detrimental and endanger limb survival if immediate further action is not taken. Neonatal thrombosis can occur even at the time of birth; thus, clinicians should be alert in cases of neonates born with pale extremities. Low-risk cases could still pose a great threat to the survival of an extremity if appropriate action is not taken.